A robust possibilistic programming approach to design a comprehensive blood supply chain based on the ABO-RH index - Taher Kouchaki Tajani; Ali Mohtashami; Maghsoud Amiri; Reza Ehtesham Rasi (تصمیم گیری و تحقیق در عملیات)
Purpose: This paper aimed to design a robust blood supply chain model that includes the stages of collection, processing and distribution of blood and blood products taking into account the lifespan and age of demand, which seeks to reduce supply chain costs and reduce the shortage and waste of blood products.Methodology: In this paper, MINLP method is used to model the research problem and in order to face the uncertainty in the problem parameters, the MPFRP method based on fuzzy data is proposed. The designed model was first evaluated for validation with numerical examples in small and large size and using real data in a case study in GAMS software?Findings: Using numerical examples and real data, the output indicates the performance of the proposed model. The output also had acceptable flexibility in the face of uncertainty in the parameters of the research model.Originality/Value: In this study, in order to reduce the shortage of blood products in situations where blood product is not available in the same group as the requested blood product, the ABO-RH adaptability principle has been used to replace the received demand with a compatible inventory. And also, to deal with uncertainty in uncertain parameters in the supply chain a solution based onmixed possibilistic-flexible robust programming is proposed.